Synergistic Effect of Two Type Cellulase Immobilized on Chitosan Microparticle as Biocatalyst for Coconut Husk Hydrolysis - Afan Hamzah; Lidya Lorenta Sitompul; Irma Nurhanifah Fenda Putri; Soeprijanto Soeprijanto; Arief Widjaja (Indonesian Journal of Chemistry, 2019)
The effectivity of employing two types of cellulases from Aspergillus niger and Trichoderma resei covalently immobilized on chitosan microparticle was investigated. Reducing sugar from CMC yielded by immobilized cellulase from T. resei alone and A. niger alone was 0.316 g/L and 0.244 g/L, respectively. Simultaneous use of both cellulases shows a significant increase of reducing sugar produced to 1.020 g/L. The effective combination of this two types of cellulases also occurred when coconut husk was used as substrate. A very high enzyme coupling of 92.06% compared to free enzyme was obtained in the immobilization. Addition of GDA not only increased enzyme coupling to 100% but also improved sugar produced. Immobilized cellulase was successfully maintained its activity until 5 cycles